Neutral pH and copper ions promote eumelanogenesis after the dopachrome stage. (5th August 2013) - Ito, Shosuke; Suzuki, Natsumi; Takebayashi, Shiori; Commo, Stéphane; Wakamatsu, Kazumasa
Summary: The diversity of pigmentation in the skin, hair, and eyes of humans has been largely attributed to the diversity of pH in melanosomes with acidic pH being proposed to suppress melanin production. Tyrosinase has an optimum pH of 7.4 and its activity is suppressed greatly at lower pH values. The first step of eumelanogenesis is the oxidation of tyrosine to dopachrome (DC) via dopaquinone. However, how eumelanogenesis is controlled by pH beyond this stage is not known. In this study, we examined the effects of pH (5.3–7.3) on the conversion of DC to 5, 6‐dihydroxyindole (DHI) and 5, 6‐dihydroxyindole‐2‐carboxylic acid (DHICA) and the subsequent oxidation of DHI and DHICA to form eumelanin. The effects of Cu 2+ ions on those reactions were also compared. The results indicate that an acidic pH greatly suppresses the late stages of eumelanogenesis and that Cu 2+ ions accelerate the conversion of DC to DHICA and its subsequent oxidation.